Chloroquine treatment induces secretion of autophagy-related proteins and inclusion of Atg8-family proteins in distinct extracellular vesicle populations - Xu, Jing; Yang, Kevin C; Go, Nancy Erro; Colborne, Shane; Ho, Cally J; Hosseini-Beheshti, Elham; Lystad, Alf H; Simonsen, Anne; Guns, Emma Tomlinson; Morin, Gregg B; Gorski, Sharon M (Autophagy, 2022)
Chloroquine (CQ), a lysosomotropic agent, is commonly used to inhibit lysosomal degradation and macroautophagy/autophagy. Here we investigated the cell-extrinsic effects of CQ on secretion. We showed that lysosomal and autophagy inhibition by CQ altered the secretome, and induced the release of Atg8 orthologs and autophagy receptors. Atg8-family proteins, in particular, were secreted inside small extracellular vesicles (sEVs) in a lipidation-dependent manner. CQ treatment enhanced the release of Atg8-family proteins inside sEVs. Using full-length ATG16L1 and an ATG16L1 mutant that enables Atg8-family protein lipidation on double but not on single membranes, we demonstrated that LC3B is released in two distinct sEV populations: one enriched with SDCBP/Syntenin-1, CD63, and endosomal lipidated LC3B, and another that contains LC3B but is not enriched with SDCBP/Syntenin-1 or CD63, and which our data supports as originating from a double-membrane source. Our findings underscore the context-dependency of sEV heterogeneity and composition, and illustrate the integration of autophagy and sEV composition in response to lysosomal inhibition. Abbreviations: ACTB: actin beta; ANOVA: analysis of variance; ATG4B: autophagy related 4B cysteine peptidase; Atg8: autophagy related 8; ATG16L1: autophagy related 16 like 1; ATP5F1A/ATP5a: ATP synthase F1 subunit alpha; CALCOCO2: calcium binding and coiled-coil domain 2; CASP3: caspase 3; CASP7: caspase 7; CQ: chloroquine; CD9: CD9 molecule; CD63: CD63 molecule; DAPI: 4',6-diamidino-2-phenylindole; DQ-BSA: dye quenched-bovine serum albumin; ER: endoplasmic reticulum; ERN1/IRE1a: endoplasmic reticulum to nucleus signaling 1; EV: extracellular vesicles; FBS: fetal bovine serum; FDR: false discovery rate; GABARAP: GABA type A receptor-associated protein; GABARAPL2: GABA type A receptor associated protein like 2; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; GO: gene ontology; HCQ: hydroxychloroquine; HSP90AA1: heat shock protein 90 alpha family class A member 1; IP: immunoprecipitation; KO: knockout; LAMP2: lysosomal associated membrane protein 2; LIR: LC3-interacting region; LMNA: lamin A/C; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MS: mass spectrometry; NBR1: NBR1 autophagy cargo receptor; NCOA4: nuclear receptor coactivator 4; NTA: nanoparticle tracking analysis; PE: phosphatidylethanolamine; PECA: probe-level expression change averaging; SDCBP/syntenin-1: syndecan binding protein; SD: standard deviation; SE: secreted; sEV: small extracellular vesicles; SQSTM1/p62: sequestosome 1; TAX1BP1: Tax1 binding protein 1; TEM: transmission electron microscopy; TMT: tandem-mass tag; TSG101: tumor susceptibility 101; ULK1: unc-51 like autophagy activating kinase 1; WC: whole cell